The Determinants of Debt and (Private) Equity Financing : The Case of Young, Innovative SMEs from Germany - Dorothea Schäfer; Axel Werwatz; Volker Zimmermann (Industry and Innovation, 2004)
Financial theory creates a puzzle. Some authors argue that high-risk entrepreneurs choose debt contracts instead of equity contracts since risky but high returns are of relatively more value for a loan-financed firm. Conversely, authors who focus explicitly on start-up finance predict that entrepreneurs are the more likely to seek equity-like venture capital contracts, the more risky their projects are. Our paper is an initial step towards resolving this puzzle empirically. We present microeconometric evidence on the determinants of debt and equity financing in young and innovative SMEs. We pay special attention to the role of risk for the choice of the method of financing. Since risk is not directly observable we use different indicators for financial and project risk. It turns out that our data generally confirms the hypothesis that the probability that a young high-tech firm receives equity financing is an increasing function of the financial risk. With regard to the intrinsic project risk, our results are less conclusive, as some of our indicators of a risky project are found to have a negative effect on the likelihood to be financed by private equity.
Additional information: This is an Accepted Manuscript of an article published by Taylor & Francis Group in "Industry and Innovation" in 2004, available online:http://dx.doi.org/10.1080/1366271042000265393
Keywords: 330; KMU; Risikokapital